Relationship between soleus H-reflex asymmetry and postural control in multiple sclerosis. Issue 4 (13th February 2022) - Cantrell, Gregory S.; Lantis, David J.; Bemben, Michael G.; Black, Chris D.; Larson, Daniel J.; Pardo, Gabriel; Fjeldstad-Pardo, Cecilie; Larson, Rebecca D.
Abstract: Background: Impaired postural control is a common symptom in people with multiple sclerosis. Multiple sclerosis frequently presents with asymmetric motor involvement. One measurement yet to be evaluated for asymmetry in people with multiple sclerosis is the soleus Hoffmann reflex. Purpose: To measure the soleus Hoffmann reflex between limbs and correlate reflex asymmetry with postural control. Material and methods: 16 participants completed four sessions of Hoffmann reflex testing and one session of balance testing. Results: Multiple sclerosis participants had significantly greater reflex asymmetry ( p = 0.01). The multiple sclerosis group had a significantly lower overall sensory organization testing composite score ( p < 0.05), indicating sensory interpretation conflict that resulted in greater postural instability. Multiple sclerosis participants produced a significantly shorter endpoint and maximum excursion ( p < 0.01) during limits of stability testing. Hoffmann reflex asymmetry was negatively related to forward endpoint excursion ( p < 0.05), maximum excursion ( p ≤ 0.01). Conclusions: Multiple sclerosis participants had greater soleus Hoffmann reflex asymmetry, which appears to significantly influence forward postural control. Implications for rehabilitation: Soleus Hoffmann reflex asymmetry appears to influence postural stability. The soleus Hoffmann reflex is capable of adapting to different modes of exercise; therefore, to reduce H-reflex asymmetry it is recommended to individualize physical rehabilitative programming. Assessing the soleus Hoffmann reflex in people with multiple sclerosis during health screenings could be of use to clinical and rehabilitative practitioners.